The Importance of Resource-based View Related Abilities and Financial Performance of SMEs for Their Sustainable Practices - Mehmet Civelek (Mehmet Akif Ersoy Üniversitesi İktisadi ve İdari Bilimler Fakültesi Dergisi)
Financial performance has always been a major concern of Small and Medium-sized Enterprises (SMEs) for their survival and sustainability practices. However, SMEs’ innovation and technological capabilities included in Resource-Based View (RBV), might stimulate their financial outcomes. Hence, this research aims to investigate the effects of innovation and technological capabilities on the financial performance of SMEs. The researcher applies a stratified random sampling method to create the research sample. Then 479 firm executives have fulfilled this survey. Furthermore, the researcher has performed Ordinal Logistic Regression tests for analysis purposes. The results confirm the negative impact of technological (patent-trademark ownership) and innovation capabilities (R&D alliances, investments and subsidies) on financial performance. R&D financing options of policy-makers, innovation and technology-related educational, and training activities of governments, universities, and certification institutions, and firms’ selection of innovative partners can stimulate firms’ innovative, technological, and financial performance and make them become more sustainable.